Writing a Letter to One’s Muse: Genre Memory and Epistolography in Carl August Thielo’s Enveloppens eller Saloppens forunderlige Hændelser (1763) - Huber, Patrizia (Scandinavistica Vilnensis, 2023)
Epistolary texts are often incorporated into 18th-century prose literature, but only rarely do they self-referentially discuss intertextuality as the mimesis of memory (Neumann 2005; 2008). Carl August Thielo’s “comic novel” uses a letter to the Muse to juxtapose a writer’s reliance on literary memoria and the demand for innovation.Drawing on Mikhail M. Bakhtin’s (1984) term “genre memory,” this paper examines the relationship between memory, generic hybridity and epistolography. Genre memory describes how, through the process of “novelization,” genres are incorporated and contemporised by the novel. Creative genre memory drives innovation by giving the most archaic generic elements a voice in narration and by establishing a ground for their hybrid interplay, thus producing a semantic surplus. By connecting this approach to epistolography, generic hybridity is illustrated as a product of material and narrative practices.In lieu of a preface to the reader, Thielo’s text begins with a Muse letter asking for assistance with the poetic work. This opens a discussion of generic differences and similarities, as well as the workings of intertextuality. At the same time, the engagement of texts with literary history is visualised via addresses to a mythical being belonging to literature’s memoria. Hence, the Muse letter depicts how poetical inventio builds on intertextuality to spark inspiration, thereby materialising the otherwise invisible, but crucial stage of writing before writing.This article serves to elaborate a first understanding of novelised epistolography and its potential for literary memory studies, which emphasises material and paratextual aspects over purely linguistic elements.
Keywords: Epistolography; genre memory; 18th century; novelization; materiality; letter; mediality; mimesis of memory; writing scene